2015
DOI: 10.1371/journal.pone.0115116
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of DAP12 in PMN Inhibits TREM1-Mediated Activation in Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease characterized by dysregulated and chronic systemic inflammatory responses that affect the synovium, bone, and cartilage causing damage to extra-articular tissue. Innate immunity is the first line of defense against invading pathogens and assists in the initiation of adaptive immune responses. Polymorphonuclear cells (PMNs), which include neutrophils, are the largest population of white blood cells in peripheral blood and functionally produce their inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
(66 reference statements)
1
11
0
1
Order By: Relevance
“…We cannot rule out that intra‐islet expression of TREM‐1—on neutrophils and monocytes—fuels the autoimmune response against the β‐cells. In addition, the TREM‐1/DAP12 pathway has also been positively associated with rheumatoid arthritis (RA)—another autoimmune disease—and studies have suggested that sTREM‐1 may in fact function as a decoy receptor in terms of competing with TREM‐1 for ligand‐binding . Contrary to this hypothesis other studies on the role of sTREM‐1 in infections and sepsis indicate that sTREM‐1 increases TREM‐1 mRNA and thereby promotes inflammation .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We cannot rule out that intra‐islet expression of TREM‐1—on neutrophils and monocytes—fuels the autoimmune response against the β‐cells. In addition, the TREM‐1/DAP12 pathway has also been positively associated with rheumatoid arthritis (RA)—another autoimmune disease—and studies have suggested that sTREM‐1 may in fact function as a decoy receptor in terms of competing with TREM‐1 for ligand‐binding . Contrary to this hypothesis other studies on the role of sTREM‐1 in infections and sepsis indicate that sTREM‐1 increases TREM‐1 mRNA and thereby promotes inflammation .…”
Section: Discussionsupporting
confidence: 85%
“…In addition, the TREM-1/DAP12 pathway has also been positively associated with rheumatoid arthritis (RA)-another autoimmune disease-and studies have suggested that sTREM-1 may in fact function as a decoy receptor in terms of competing with TREM-1 for ligand-binding. 31,32 Contrary to this hypothesis other studies on the role of sTREM-1 in infections and sepsis indicate that sTREM-1 increases TREM-1 mRNA and thereby promotes inflammation. 14 Both findings could also be supported by our study.…”
Section: Discussionmentioning
confidence: 92%
“…TREM1 is similar to TREM2 in that it also signals through DAP12; however, whereas TREM2 regulates osteoclast differentiation, TREM1 controls inflammation and induces secretion of pro-inflammatory cytokines from polymorphonuclear cells (PMNs) [81]. PMNs isolated from RA synovial fluid and blood express increased levels of TREM1 and DAP12 compared to healthy patients [82]. Furthermore, expression is significantly enhanced in healthy donor PMNs after 24-hour stimulation with TNF, IL-6, or IL-17.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Soluble TREM-1 was shown to be elevated in serum and expressed on CD68 + macrophages in the intestinal lamina propria in patients with acute and chronic IBD (25,27). Recently, isolated PBMCs from primary specimens of patients with rheumatoid arthritis showed an increased expression of TREM-1, with a subsequent increased activation of ERK and MAP kinases, secretion of IL-8 and RANTES (28). This result further supports the relevance of our findings, which link TREM-1 to MAP kinase signaling, IL-8 and RANTES in "subchronic" inflammatory conditions.…”
Section: Factor Analysis Identified Cinc1-3 Mip-1/3` Mig Rantes Anmentioning
confidence: 99%